Intestinal stoma as a result of surgery - Monika Pierzak; Martyna Gorzelak (Kazimierz Wielki University, 2017)
Admission: The history of the emergence of artificial fistula counts nearly 300 years. The first stoma were selected in a targeted manner in 1776. Estimates indicate that the number of intestinal fistulas performed in our country is around 6 thousand. per year, it is estimated that people living with a stoma is about 20 thous. of which the majority are women[1]. Intestinal stoma of the Latin language. preaternaaturalis anus is opening. It is produced in the conditions in which it is necessary to cut or a corresponding decompression intestine[2]. People who were selected as a result of disease stoma are afraid of how they will function in daily life. The aim of the work is to illustrate the issues concerning the stoma, including, history, epidemiology, etiopathogenesis, complications, frequency and quality of life of patients with stoma.   Key words: intestinal stoma, quality of life, surgery [1]Cierzankowska K .: The lesions around stomii- prevention and treatment. "Proctology, Supplement. V Symposium of Polish Club of Colon and Rectal "2005, p. 48-49. [2]Ułańska J Wild A Kołomecki K. ambulatory care for patients with a stoma. Post Valetudinaria- Forces Med Klin 2004; 9, 87-92.